Reforming in a difficult macroeconomic context A review of the issues and recent literature - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2016)
This paper reviews the main issues related to the short-term impact of structural reforms in different macroeconomic contexts and takes stock of existing theoretical and empirical studies. Taking reforms introduced in "normal" times as a benchmark, it reviews the available evidence on the impact of reforms that are implemented in "bad" times - i.e. in the presence of a sizeable negative output gap and persistently weak demand - as well as under different assumptions regarding the availability or effectiveness of macroeconomic policies in supporting the reforms. In doing so the paper focuses on the key channels through which different reforms influence short-term activity via the main components of demand and discusses how these channels operate under different macro conditions. Overall, the evidence suggests that in a context of weak demand, structural reform strategies will have significantly better chances of being successful if they put more weight on measures that in addition to stimulate employment or productivity in the medium term can best support demand in the short term